2018
DOI: 10.1002/alr.22086
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of two consecutive nasal respiratory cycles: toward a better understanding of nasal physiology

Abstract: CFD is more efficient and reliable when the entire respiratory cycle is simulated and repeated to avoid losing information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 47 publications
1
11
0
1
Order By: Relevance
“…Most of the flow went through the lower part of the olfactory cleft and middle meatus. These findings have been confirmed by others who found that nasal resistance and shear stress on the wall reached a peak in the region of the nasal valve (22) , and the values of nasal resistance measured by rhinomanometry were similar to those found using CFD (23) .…”
Section: Airflowsupporting
confidence: 86%
“…Most of the flow went through the lower part of the olfactory cleft and middle meatus. These findings have been confirmed by others who found that nasal resistance and shear stress on the wall reached a peak in the region of the nasal valve (22) , and the values of nasal resistance measured by rhinomanometry were similar to those found using CFD (23) .…”
Section: Airflowsupporting
confidence: 86%
“…Therefore, studies related to the nasal valve can be included in CFD analyses of the nasal cartilage. CFD showed that the nasal valve area accelerated the airflow owing to its resistance to airflow, 103 , 104 and the pressure calculated by the computer was similar to the clinical pressure measurement. 105 Changes in the cartilage, such as the collapse of the nasal cartilage and displacement of the nasal septum, can affect the nasal valve area, 106 – 109 which would influence the patterns of airflow.…”
Section: Computational Simulation Technology In Clinical Research Of mentioning
confidence: 53%
“…Computational fluid dynamics studies demonstrate that all nasal regions are reached when using a head tilt position of 45 °C forward for NL, 17 especially with large-volume irrigations, 18 suggesting good mechanical efficiency of NL in washing the nose.…”
Section: What Are the Potential Benefits Of Nl To Covid-19 Patients?mentioning
confidence: 98%